Социальный капитал: теоретические основания исследования и операциональные параметры - Демкив, О. (Социология: теория, методы, маркетинг, 2004)
The author distinguishes three different levels of the social capital phenomenon
interpretation, underlines a crucial role of the social network phenomenon for systemic
vision of the social capital and analyses possibilities of application of social network
analysis methodology to the study of social capital.